Hubungan Asupan Energi terhadap Pertumbuhan dan Perkembangan Balita Usia 24 - 59 Bulan - Supriadi, Rizky Febriyanti; Mahardany, Beauty Octavia; Amin, Erna (Mando Care Jurnal, 2025)
Early childhood is a critical period for cellular growth that highly depends on adequate nutritional intake to prevent irreversible impacts on physical and cognitive capacities. This study aims to analyze the correlation between energy intake and the growth and development status of toddlers in Mamuju Regency. This was an analytical observational study with a cross-sectional design involving 30 toddlers aged 24–59 months selected through purposive sampling. Energy intake data were collected using a 7-day food record method, growth was measured via anthropometry (Z-score), and development was assessed using the KPSP (Developmental Pre-Screening Questionnaire) instrument. Data were analyzed using Spearman’s Rho correlation and Fisher’s Exact significance tests with a 95% confidence level. The results showed that the majority of respondents experienced an energy deficit, particularly in the 4-5 year age group (80%). There was a strong significant correlation between energy intake and WAZ (Weight-for-Age) indices (p=0.01; r=0.642), HAZ (Height-for-Age) indices (p=0.000; r=0.684), and child development levels (p=0.023; r=0.524). However, no significant correlation was found between energy intake and body proportionality or the WHZ (Weight-for-Height) index (p=0.545), indicating a homeostatic adaptation phenomenon of being short but proportional. This study concludes that daily energy intake is a primary determinant that simultaneously dictates the quality of physical growth and the maturity of central nervous system functions in toddlers.